Impact of living patterns and social participation on the health vulnerability of urban and rural older persons in Jiangsu Province, China - Juan Zheng; Jianqiang Xu; Yuhang Wu; Daqi Liu (BMC Geriatrics, 2025)
Abstract Background This study analyzes the influence of living patterns and social participation on the health vulnerability of older people in urban and rural areas and provides a reference for addressing this vulnerability. Methods A total of 3500 participants aged 60 years and above from Jiangsu Province, China, were surveyed. The vulnerability index, which evaluates self-rated health, risk of falling, general pain or discomfort, chronic diseases, emotional characteristics, depression, anxiety, is used to measure health vulnerability. A multiple linear regression model is used to evaluate the effects of living patterns and social participation on health vulnerability. Results A certain level of health vulnerability exists among Chinese urban and rural older people. Living with family members has a positive effect on their health. Individuals who live alone have worse health and lower subjective well-being. Social participation significantly reduces the comprehensive levels of general health vulnerability, physical health vulnerability, and mental health vulnerability of older people. For urban older people, living with families reduces the level of physical and mental health vulnerability, whereas living alone significantly increases health vulnerability. Living patterns significantly affect the psychological vulnerability of rural older people. Social participation has an important impact on the health of older people who live alone, especially on the mental health vulnerability of older people who live alone in urban areas. Conclusion Living patterns and social participation are important factors that affect the health vulnerability of older people in both urban and rural areas. Social participation has a significant effect on the health of older people who live alone. In particular, for older people who live alone in cities, being socially active can help change their “sedentary” lifestyle, thereby promoting physical and mental health and reducing vulnerability.